De novo assembling a complete mitochondrial genome of Pedicularis rex (Orobanchaceae) using GetOrganelle toolkit. Issue 1 (2nd January 2020) - Li, Xin; Lin, Chun-Yan; Yang, Jun-Bo; Yu, Wen-Bin
Abstract: We reported the first mitogenome of Pedicularis from P. rex (Orobanchaceae), which is endemic to SW China. The complete mitochondrial genome (mitogenome or chondriome) was a single circular chromosome that was 219, 859 bp in length. It contains 56 genes, including 34 protein-coding ( cox2 and atp9 with two copies), 19 transfer RNA (tRNA), and three ribosomal RNA (rRNA) genes. Phylogenetic analysis showed that Pedicularis rex was closely related to Castilleja paramensis .